La amistad en la patrística y el mundo medieval. - Muñoz Medina, Ceferino (Scripta Mediaevalia, 2025)
The article "Friendship in Patristics and the Medieval World" from the journal Scripta Mediaevalia addresses the importance of friendship in philosophical, theological, and literary reflection from Antiquity to the Middle Ages. It highlights the realization of a workshop at the National University of Cuyo in Argentina, where scholars from Argentina and Chile debated on the topic. Six papers are presented that explore friendship from different philosophical and theological perspectives, focusing on authors such as Cicero, Saint Augustine, Alcuin of York, and Thomas Aquinas.